Microalbuminuria as a Predictor of Pregnancy Induced Hypertension - Kour, G; Kour, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to find out predictive value of microalbuminuria between 24-34 weeks of gestation in the development of pregnancy-induced hypertension, maternal and fetal complications. Methods: Urinary microalbuminuria was measured by turbidometry in 200 normo-tensive women between 24-34 weeks of gestation. Microalbuminuria was defined as a value of ≥ 20 mg albumin per gram of creatinine in a spot sample of urine. The women were divided into two groups as microalbuminuria positive and microalbuminuria negative. They were followed up to delivery and were evaluated for the development of pregnancy-induced hypertension, maternal and fetal complications. Results: Out of 200 women microalbuminuria was positive in 32 (16%) patients. Sixteen (50%) in the microalbuminuria group developed hypertension as compared to seven (4.1%) in the microalbuminuria negative group (p<0.0001). Also 13 (40%) in the microalbuminuria positive group developed a maternal complication as compared to 11 (6.5%) in the microalbuminuria negative group (p<0.0001). Nineteen women (59%) in the microalbuminuria group had a fetal complication as compared to 10 women (5.9%) in the microalbuminuria negative group (p<0.0001). Conclusions: Presence of urinary microalbuminuria between 24-34 weeks of gestation can predict development of pregnancy-induced hypertension, maternal and fetal complications. DOI: http://dx.doi.org/10.3126/njog.v9i2.11761